PENGARUH MODAL, JAM KERJA, DAN PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS)TERHADAP PENDAPATAN PEDAGANG DI PASAR BURUNG SATRIA, BALI - Natalia, Alyssa Dea; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
This study aims to obtain empirical evidence regarding the effect of capital, working hours, and the use of the Indonesian Standard Quick Response Code (QRIS) on the income of traders at the Satria Bird Market, Bali. This study uses a quantitative research method in the form of associative. The population in this study were traders at the Satria Bird Market, Bali. The number of traders is as many as 90 traders. The method of determining the sample used is a saturated sample in which the entire population becomes the sample in the study. Data collection was carried out by observation and structured interviews using a list of questions in a questionnaire to 90 traders at the Satria Bird Market, Bali. In this study, multiple linear regression analysis was used to examine the effect of capital, working hours, and the use of QRIS on the income of traders at the Satria Bird Market, Bali. The results showed that the use of capital, working hours, and the use of QRIS had a positive and significant effect on the income of traders at the Satria Bird Market, Bali. The implication of this research is to increase the income of traders in the satria bird market, it is hoped that traders can add their capital, working hours, and use of their QRIS. Because adding these three variables will have a positive effect on the income of traders in the warrior bird market. Keyword : capital, working hours, use of QRIS, traders, and income